2015
DOI: 10.1152/ajpgi.00409.2014
|View full text |Cite
|
Sign up to set email alerts
|

Induction of rhythmic transient depolarizations associated with waxing and waning of slow wave activity in intestinal smooth muscle

Abstract: Cannon described in 1902 the segmentation motor activity of the small intestine (Canon WB. J Med Res 7: 72-75, 1902). This motor pattern can arise when low-frequency transient depolarizations are evoked in the interstitial cells of Cajal associated with the deep muscular plexus (ICC-DMP) network, which then affect the omnipresent slow wave activity: changing its regular amplitude into a waxing and waning pattern. The objective of the present study was to investigate physiological stimuli that could induce the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 29 publications
(34 reference statements)
0
11
0
Order By: Relevance
“…In the small intestine, the classical segmentation motor activity is generated when the ICC associated with the deep muscular plexus (ICC-DMP) produce a stimulus-dependent rhythmic electrical activity. 34,35 In the rat colon, it is the ICC-MP that generates a stimulus-dependent low frequency activity; the laboratories of Jimenez in the rat 31 and Takaki in the mouse 36 showed that ICC-MP are associated with a low frequency pacemaker that can drive contractions at frequencies from 0.3 to 2 cpm, 19,21,22,[31][32][33] hence the on/off pattern observed in the present study is likely to be associated with pacemaking from the ICC-MP. It is not known where the ultra-slow pacemaker that drives the slow propagating segmental contractions is located; it may be within the ENS or in the intramuscular ICC (ICC-IM).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…In the small intestine, the classical segmentation motor activity is generated when the ICC associated with the deep muscular plexus (ICC-DMP) produce a stimulus-dependent rhythmic electrical activity. 34,35 In the rat colon, it is the ICC-MP that generates a stimulus-dependent low frequency activity; the laboratories of Jimenez in the rat 31 and Takaki in the mouse 36 showed that ICC-MP are associated with a low frequency pacemaker that can drive contractions at frequencies from 0.3 to 2 cpm, 19,21,22,[31][32][33] hence the on/off pattern observed in the present study is likely to be associated with pacemaking from the ICC-MP. It is not known where the ultra-slow pacemaker that drives the slow propagating segmental contractions is located; it may be within the ENS or in the intramuscular ICC (ICC-IM).…”
Section: Discussionmentioning
confidence: 53%
“…We have shown that substance P can evoke the ICC-DMP pacemaker. 43 Potential stimuli are not limited to neurotransmitters; fatty acids such as butyrate and decanoic acid can also evoke the low frequency pacemaker activity, 34 and so can distention. 44 Siegle and Ehrlein's observation that neurotensin can evoke segmentation can be explained by the induction of ICC-DMP pacemaker activity.…”
Section: Discussionmentioning
confidence: 99%
“…4Ba, shows a waxing and waning pattern which has been extensively described elsewhere. 22 A CWT time-frequency plot indicated that this pattern was composed of two different frequency signals, 2 and 28 cpm (Fig. 4Bb).…”
Section: Recording From Circular Muscle That Includes Icc-mp and Icc-dmpmentioning
confidence: 96%
“…With ICC-MP present, slow wave activity was recorded at 15-28 cpm (21.1 AE 4.3 cpm; n = 15) as shown previously. 2,21,22 In addition, we recorded two types of electrical activities that included a low frequency component when recorded close to the ICC-DMP. Fig.…”
Section: Recording From Circular Muscle That Includes Icc-mp and Icc-dmpmentioning
confidence: 99%
“…But in that case, the maximum amplitude becomes twice the original amplitude. When we confi rmed the induction of waxing and waning by intracellular recording of the electrical activity, no change in maximum slow wave amplitude occurred (Pawelka and Huizinga 2015 ). Suzuki deduced the existence of two prominent similar frequencies in the waxing and waning pattern based on FFT analysis but FFT might not be the best method to evaluate frequencies in a signal that changes markedly over time.…”
Section: Expanding the Role Of Icc In Control Of Motility: The Segmenmentioning
confidence: 92%